Time Course of Metabolomic Alterations in Cerebrospinal Fluid After Aneurysmal Subarachnoid Hemorrhage - Ho, Wing Mann; Görke, Alice S.; Glodny, Bernhard; Oberacher, Herbert; Helbok, Raimund; Thomé, Claudius; Petr, Ondra (Frontiers in Neurology, 2020)
Object: The aim of this study was to investigate metabolite levels in cerebrospinal fluid (CSF) in their time-dependent course after aneurysmal subarachnoid hemorrhage (aSAH) comparing them to patients harboring unruptured intracranial aneurysms. Methods: Eighty CSF samples of 16 patients were analyzed. The study population included patients undergoing endovascular/microsurgical treatment of ruptured intracranial aneurysms (n = 8), which were assessed for 9 days after aSAH. Control samples were collected from the basal cisterns in elective aneurysm surgery (n = 8). The CSF samples were consecutively collected with extraventricular drain (EVD) placement/intraoperatively, 6 h later, and daily thereafter (day 1–9). The endogenous metabolites were analyzed with a targeted quantitative and quality controlled metabolomics approach using the AbsoluteIDQ®p180Kit. Differences inbetween timepoints and compared to the control group were evaluated. Results: Numerous alterations of amino acid (AA) levels were detected within the first hours after bleeding. The highest mean concentrations occurred 1 week after aSAH. AA levels were continuously increasing over time starting 6 h after aSAH. Taurine concentration was highest briefly after aSAH starting to decrease already after 6 h (vs. day 1–9, p = 0.02). The levels of sphingomyelins/ phosphatidylcholines/ lysophosphatidylcholines/mono-unsaturated fatty acid chain were highly elevated on day 0 (compared to other timepoints or controls, p < 0.01) and decreased over the next several days to concentrations comparable to the control group. Carnitine concentrations were decreased after SAH (vs. day 7, p < 0.01), while they recovered within the next day. The Fischer ratio of branched-chain AA to aromatic AA was lowest immediately after SAH and increased in 7 days (p < 0.001). Conclusion: AA levels in CSF increased overtime and often differ from patients without SAH. There was a peak concentration of structural AA within the first 6 h after aneurysm treatment. Time-dependent alterations of CSF metabolites and compounds may elucidate pathophysiological processes after aSAH, providing potential predictors assessed non-invasively by routine lab testing.